Tahfiz Qur’an dengan Metode Tasmi’ dan Sambung Ayat (Strategi Pengorganisasian, Penyajian, dan Pengelolaanya di Pondok Pesantren Al-Lathifiyyah Palembang) - Anindya Diah Hartanti; Abdurrahmansyah Abdurrahmansyah; Muhammad Adil (STAI Serdang Lubuk Pakam, 2021)
This study aims to analyze the strategy of organizing, presenting, and managing the tasmi' method and connecting verses in memorizing the Qur'an at the Al-Lathifiyyah Islamic Boarding School. This research uses qualitative research methods based on descriptive studies. Data collection techniques using observation techniques, interviews, and documentation. Data analysis used steps of data reduction, data presentation, and data verification. Data verification is done by using triangulation technique which compares data from three instruments and three different data sources. The results showed that the organization of this method was carried out by organizing the curriculum and memorization material starting from juz 1, where tasmi' was carried out in half juz to one juz instead of persurat. Organizing is carried out starting from planning, determining success indicators, objectives, materials, media, implementation steps and assessments. While the management is carried out in several stages, namely the acceptance of new students, the tahsin stage, the bin-nazhar stage, the tahfizh stage, the talaqqi stage, the Takrir stage, the tasmi stage, and the verse continuation stage.